1987
DOI: 10.1128/mcb.7.8.2735
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a cellular protein to the gibbon ape leukemia virus enhancer.

Abstract: The gibbon ape leukemia virus (GALV) contains enhancer activity within its long terminal repeat. In the GALV Seato strain this activity resides in a 48-base-pair (bp) repeated element. We demonstrate the existence of a cellular protein which binds in this region of the Seato strain. A sensitive method for enriching protein-DNA complexes from crude extracts coupled with exonuclease and DNase footprint analysis revealed the specific binding of this protein to a 21-bp region within each repeated element. A 22-bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Even though it appears that the common Int8 VNTR alleles differ by only one perfect repeat unit, it has been demonstrated that the on͞off rate for transcription factors in recognizing their cognate binding sites in tandem repeats can be affected by the copy number of those repeats (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Even though it appears that the common Int8 VNTR alleles differ by only one perfect repeat unit, it has been demonstrated that the on͞off rate for transcription factors in recognizing their cognate binding sites in tandem repeats can be affected by the copy number of those repeats (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments revealed the presence of factors that specifically recognize the GALV enhancer AP1 site in MLA144 gibbon T and HeLa cells (27). In extracts from each line, mobility shift analysis resolved several complexes with the GALV-AP1 probe (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Binding-reaction mixtures contained a 32P-3 '-end-labeled double-stranded oligonucleotide probe. (27). The shift labeled +-2 results from interaction of the specific complex with the antibody; note the disappearance of the specific shift with HeLa extract.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations